The epiMelanoma test enables plasma-based detection of melanoma and prediction of immunotherapy response - Olivia Dumas; Nicholas Rozza; David Cheishvili; Sharon Luk; Sarah T. K. Sin; Alua Khassenova; Richard Kremer; Moshe Szyf; Catalin Mihalcioiu; Shafaat A. Rabbani (Scientific Reports)
Abstract Background Melanoma is one of the most serious skin cancers worldwide, often progressing without obvious symptoms. Early detection is crucial to enable timely intervention, reducing morbidity and mortality. However, no standardized high-throughput test exists for non-invasive melanoma detection. Methods This diagnostic study aimed to develop and validate a high-throughput targeted DNA methylation-based test for detecting melanoma in cell-free DNA (cfDNA) from plasma and predicting response to immune checkpoint inhibitors (ICIs). A multiplexed next-generation sequencing assay targeting these five melanoma-specific DNA regions, named epiMelanoma, was developed and tested on a clinical cohort of 199 participants, including 121 melanoma patients (stages I-IV) from oncology clinics and 78 healthy donors sourced from biorepositories. Plasma cfDNA was collected from 187 participants, and biopsies from 35 patients. Results Here we show that epiMelanoma shows high classification accuracy in both biopsies and plasma cfDNA. First, four DNA regions categorically methylated across diverse cancers, including melanoma, but unmethylated in other tissues, were identified using TCGA and GEO datasets (n = 160), showing high classification accuracy (AUC = 0.9987, sensitivity 98.67%, specificity 100%). A fifth melanoma-specific region was discovered (cg04652957, sensitivity 100%, specificity 90.91%) and validated in 5479 samples. In clinical samples, sensitivity for early- and late-stage melanoma was 27% and 60%, respectively, with high specificity (98.15%). Sensitivity in biopsies exceeded 90%. Furthermore, a significant correlation was observed between the methylation signature and response to ICIs (p = 0.012), with lower M-scores associated with improved overall survival (log-rank p = 0.001, Kaplan–Meier). Conclusions The epiMelanoma assay represents a promising non-invasive tool for early melanoma detection and personalized treatment, by enabling timely intervention and identifying patients most likely to benefit from immunotherapy, and therefore, potentially improving patient outcomes and reducing healthcare burdens.